HYDROGENOLYSIS OF PALM OIL DERIVED METHYL ESTERS OVER NIOBIUM AND TUNGSTEN BASE CATALYSTS - MARINESCU, Mihai; CIUPARU, Dragoș Mihael; BOMBOȘ, Dorin; DUȘESCU-VASILE, Cristina Maria; POPOVICI, Roxana Daniela; MATEI, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2023)
Vegetable oils are widely available in nature and are one of the most important sustainable feedstocks for biofuel production. W/Pd/γ-Al2O3-ZnZSM-5 and Nb/Pd/γ-Al2O3-ZnZSM-5 catalysts where prepared, characterized and tested in the hydrogenolysis reaction of palm oil fatty acid esters. The catalysts were characterized by determining the textural characteristics, the thermal stability, and the nature of the acidic sites. The appearance of particle agglomerations was evaluated by scanning electron microscopy (SEM). The resulting reaction products were n-aliphatic hydrocarbons, iso-aliphatic hydrocarbons, cycloaliphatic hydrocarbons, and arenes. No oxygenated organic compounds were identified in the collected liquid phase. At lower pressures, the deoxygenation process occurs to approximately 33% through the hydrogenation of the carboxylic bond and to approximately 67% through decarboxylation/decarbonylation, while at higher pressure than 60 bar the deoxygenation process proceeds preferentially through decarboxylation/decarbonylation.